Study of Dramaturgy Applied by The Selected Bureau of Architectural Consultants in Indonesia - Amir, Hasaruddin; Hatta, Asta Juliarman; Abidah, Andi (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2021)
Every architect has a different view and thought about something in designing a building. The basis of ideas design to a building is gained from experience, imagination, creativity, education, etc. Every professional architect also owns cognitive to express how the architecture works implemented through the design of a building. In architecture, there is a theory that connects drama and architecture in everyday life, dramaturgy. This article aims to see the concepts of dramaturgy in the works of the architectural consulting bureau responsible for, Omah Boto building, Aceh Tsunami Museum, and Phinisi Unm Tower. This study uses a qualitative method with data collection carried out using literature studies. Furthermore, the analyzed data is then presenting in descriptive for a more informative series. Data analysis aims to explore the relevance of the dramaturgy application in architecture to the thinking of architects in Indonesia. The results of the study show dramaturgy in architecture is used as a match between contemporary theater art and architecture. All three architectural consultants have used elements of dramaturgy in the design process. The three architectural consultants have used aspects of dramaturgy in their design process. The application of the basic concepts of dramaturgy used is an exterior setting of the building, Goals or ideas, building layout settings, visual instructions, and motion direction.